From #Hashtags to Legislation : Engagement and Support for Economic Reforms in the Gulf Cooperation Council Countries - Arezki, Rabah (World Bank, Washington, DC, 2022)
Ownership of reforms by citizens is often presented as important for success. This paper explores media engagement and support for economic reforms in the Gulf Cooperation Council countries using text analysis techniques on publicly available sources. The results show that while reform efforts have intensified in recent years in the Gulf Cooperation Council countries, these efforts tend to focus on stronger rather than weaker policy areas, potentially limiting the growth-enhancing effect of reforms. Social media analysis using Twitter shows that the population's support for reforms has been declining. The analysis of traditional news media points to more engagement by international than by local media. However, sentiment from international media is less positive about economic reforms in the Gulf Cooperation Council countries. Sentiment in international media and social media matters, as evidenced by its positive and strong correlation with foreign direct investment inflows into the Gulf Cooperation Council countries.